Fast and Inexpensive Separation of Bright Phosphor Particles from Commercial Sources by Gravitational and Centrifugal Sedimentation for Deep Tissue X-ray Luminescence Imaging - Mohammad Arifuzzaman; Meenakshi Ranasinghe; Apeksha C. Rajamanthrilage; Sriparna Bhattacharya; Jeffrey N. Anker (Photonics, 2022)
X-ray luminescence tomography (XLT) detects X-ray scintillators contrast agents using a focused or collimated X-ray beam to provide high spatial resolution excitation through thick tissue. The approach requires bright nanophosphors that are either synthesized or purchased. However, currently available commercial nanophosphors are mostly composed of a polydisperse mixture of several micro- to nano-sized particles that are unsuitable for biomedical imaging applications because of their size and aggregated form. Here, we demonstrate a fast and robust method to obtain uniform nano to submicron phosphor particles from a commercial source of polydisperse Eu- and Tb-doped Gd2O2S particles by separating the smaller particles present using gravitational and centrifugal sedimentation. In contrast to ball milling for 15–60 min, which drastically degraded the particles’ brightness while reducing their size, our sedimentation method enabled the extraction of comparatively bright nanophosphors (≈100–300 nm in size) with a luminescence intensity of ≈10–20% of the several micron particles in the sample. Moreover, if scale up for higher yielding is required, the sedimentation process can be accelerated using fixed-angle and/or swinging bucket rotating centrifugation. Finally, after separation and characterization, nano and submicron phosphors were suspended and imaged through 5 mm thick porcine tissue using our in-house-built scanning X-ray induced luminescence chemical imaging (XELCI) system.